2011
DOI: 10.1055/s-0031-1296395
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence Study of Two Fixed Dose Combination Tablet Formulations of Lopinavir and Ritonavir in Healthy Volunteers

Abstract: The study was designed to compare the rate and extent of absorption of two fixed dose combination tablet formulations of lopinavir (CAS 192725-17-0) and ritonavir (CAS 155213-67-5). This bioequivalence study was conducted using a standard preparation as reference and a generic alternative as test in 72 adult healthy volunteers within 18-45 years of age who received a single dose of the test or reference product under fasting conditions. A washout period of 10 d was maintained between period I and period II dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The LLOQ was 25 ng/mL for lopinavir, which was markedly lower than 62.5 ng/mL [ 31 ] and 100 ng/mL [ 35 ] reported in the literature; and 5 ng/mL for ritonavir, which was lower than 12.5 ng/mL [ 31 ] and 99 ng/mL [ 36 ] reported in the literature. The RE values of lopinavir and ritonavir at the LLOQ were 3.45% and 1.46%, and the RSDs were 4.03% and 4.32%, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…The LLOQ was 25 ng/mL for lopinavir, which was markedly lower than 62.5 ng/mL [ 31 ] and 100 ng/mL [ 35 ] reported in the literature; and 5 ng/mL for ritonavir, which was lower than 12.5 ng/mL [ 31 ] and 99 ng/mL [ 36 ] reported in the literature. The RE values of lopinavir and ritonavir at the LLOQ were 3.45% and 1.46%, and the RSDs were 4.03% and 4.32%, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…[32] A bioequivalence study is usually conducted using a randomized, two-period, two-treatment, crossover design that allows comparison within individual healthy volunteers. [33] Hill and colleagues compared the bioequivalence of sofosbuvir and daclatasvir from seven pharmaceutical companies worldwide and concluded that they were all bioequivalent. [20] Finally, generic drugs must show label equivalence, which means that the indications are the same as the originator product.…”
Section: Discussionmentioning
confidence: 99%